2018
DOI: 10.15441/ceem.16.163
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of abnormal brain computed tomography findings in patients with acute altered mental status in the emergency department

Abstract: ObjectiveBrain computed tomography (CT) is commonly performed to diagnose acute altered mental status (AMS), a critically important symptom in many serious diseases. However, negative CT results are common, which result in unnecessary CT use. Therefore, this study aimed to determine the clinical factors associated with positive CT findings.MethodsPatients with acute AMS selected from an emergency department-based registry were retrospectively evaluated. Patients with non-traumatic and noncommunicable diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“…The slight difference could be attributed to differences in enrollment criteria: we included febrile patients down to a slightly lower age (65 years) and also included MRI for detecting ABI. Another study reported that hemorrhage, infarction, and tumor were the most common final diagnoses [14]. Our results are in agreement with that study.…”
Section: Plos Onesupporting
confidence: 93%
See 3 more Smart Citations
“…The slight difference could be attributed to differences in enrollment criteria: we included febrile patients down to a slightly lower age (65 years) and also included MRI for detecting ABI. Another study reported that hemorrhage, infarction, and tumor were the most common final diagnoses [14]. Our results are in agreement with that study.…”
Section: Plos Onesupporting
confidence: 93%
“…Shin et al . [ 14 ] concluded that a focal neurological deficit or a GCS < 9 and C-reactive protein < 2 mg/dL are closely related to abnormal findings in brain CT. In line with that study, we found that a lateralizing sign and GCS were predictive factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shin et al . [30] in their study found that the presence of focal neurological deficit, C-reactive protein level <2 mg/dl, and Glasgow Coma Scale <9 is associated with positive findings on brain CT in patients with altered sensorium. Our study showed that 69.09% of had no significant findings which was consistent with Shin et al .…”
Section: Discussionmentioning
confidence: 99%